Dynamic Resource Reservation and Connectivity Tracking to Support Real-Time Communication among Mobile Units. Issue 5 (12th December 2005) - Facchinetti, Tullio; Buttazzo, Giorgio; Almeida, Luis
Abstract : Wireless communication technology is spreading quickly in almost all the information technology areas as a consequence of a gradual enhancement in quality and security of the communication, together with a decrease in the related costs. This facilitates the development of relatively low-cost teams of autonomous (robotic) mobile units that cooperate to achieve a common goal. Providing real-time communication among the team units is highly desirable for guaranteeing a predictable behavior in those applications in which the robots have to operate autonomously in unstructured environments. This paper proposes a MAC protocol for wireless communication that supports dynamic resource reservation and topology management for relatively small networks of cooperative units (10–20 units). The protocol uses a slotted time-triggered medium access transmission control that is collision-free, even in the presence of hidden nodes. The transmissions are scheduled according to the earliest deadline first scheduling policy. An adequate admission control guarantees the timing constraints of the team communication requirements, including when new nodes dynamically join or leave the team. The paper describes the protocol focusing on the consensus procedure that supports coherent changes in the global system. We also introduce a distributed connectivity tracking mechanism that is used to detect network partition and absent or crashed nodes. Finally, a set of simulation results are shown that illustrate the effectiveness of the proposed approaches.